HISTORY EDUCATION AS AN EDUCATIONAL MEDIUM TO EMBODY THE SPIRIT OF NATIONALITY - Hasan, Said Hamid (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2011)
The above objectives of history education clearly indicate that history education aims at the development of students awareness of time concept; scientific knowledge of the society in the past in terms of their values, ways of thinking, attitudes and achievement; skills for understanding and generating knowledge of the past; attitudes towards history as what happened in the past society, and history as a science that reconstruct the past . To put it in a simple way the objectives suggest that students should have knowledge about the past scientifically and this knowledge is gained through the application of historical thinkings and skills. The objectives also suggest that history education should prepare students for their roles as a citizen who loves and is proud of the country, the nation and their past achievement. Further, the objectives place history as an education media for preparing the students for their future lives. Big potential of historical education is developing the nation’s identity. Historical education is a vehicle that gives opportunities for young generations to conduct self identification as a member of this nation. History education potential in developing the nation with heroism,leadership, and willingness to sacrifice.